Aplikasi Pre-Heating dan Edible Coating untuk Peningkatan Kualitas Keripik Kentang - Adolf Parhusip; Aileen Neysha; Lincoln Halim; Fernando Ogyen Iwantoro (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2021)
This study aimed to improve the crispness and to reduce oil absorption in potato chips. Potato chips crispness was improved by applying pre-heating, namely boiling and steaming before frying, while oil absorption was reduced by adding acacia gum as an edible coating. Boiling and steaming was conducted at 100°C for 0, 2, 3, 4, 5, and 6 minutes. Acacia gum (0, 3, 4, 5, and 6%) and calcium chloride (0, 0.5, and 1%) were added in the formulation. Boiling for 4 minutes yielded hardness of 384.902±25.10 g, moisture content of 3.02±0.07%, crispness score of 5.04±0.60 (crispy), and overall hedonic score of 5.10±1.43 (somewhat like). Further process by adding acacia gum 5% and calcium chloride 1% yielded potato chips with fat content of 28.01±1.56%, oil absorption ratio of 0.32±0.03, moisture content of 1.07±0.78%, and hardness level of 411.111±25.32 g. The products recuded oil absorption during frying up to 41.81±5.86%.